Bessel beams of laser-driven two-level atoms - Hayrapetyan, Armen; Fritzsche, Stephan (Physica scripta, 2013)
We study Bessel beams of two-level atoms that are coupled to a linearly polarized laser field. For such atom beams, we construct exact Bessel-type solutions of the Schrödinger equation beyond the paraxial approximation for beam propagation. In particular, we examine the probability density for Bessel beams of neutral two-level atoms driven by a laser field but without the level damping being taken into account. We show how the radial dependence of the probability density (from the beam axis) can be affected by tuning the parameters of the atom-laser system, such as the resonant frequency and amplitude of the laser field and/or the nuclear charge and velocity of the atomic beam.